PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) PESERTA DIDIK BERBASIS MULTIPLE INTELLIGENCES UNTUK MELATIH KETERAMPILAN BERPIKIR KREATIF PADA MATERI SISTEM EKSKRESI MANUSIA KELAS VIII SMP - Aulia Dwi Utami; Mariani Natalina; Yustina Yustina (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study aims to produce quality student worksheets based Multiple Intelligences and to train creative thinking skills on the material of the excretion system in humans for grade VIII of junior high school. This research was carried out in the Biology Education Laboratory of the Faculty of Teacher Training and Education, University of Riau and the state junior high school 4 Pekanbaru in September 2019-May 2020. The type of research used is Research and Development (R&D) with the ADDIE’s model and was carried out in 5 stages, namely analysis, design, development, implementation and evaluation. In his research, we does by developments phase. Data collection instruments in the form of validation sheets and respondent sheets. The results of the LKPD based Multiple Intelligences to train creative thinking skills validation are at an average value of 3.67 with a very valid category. The results of a limited test score are 3.45 with a very good category. It can be conclude that LKPD based Multiple Intelligences to train creative thinking skills on the material of the excretion system in humans for grade VIII of junior high school that have been developed are categorized as quality and feasible to be implemented on a broader scale.Key Words: Student’s Worksheet, Multiple Intelligences, Creative Thinking Skills